ROLE OF JALAKUMBHI IN UTERINE FIBROID - A CLINICAL STUDY - Murthy, *Seema; Arawatti, Siddaram; Rai, Pankaj; Biswal, Debasis; Nibedita, Mohapatra (International Journal of Ayurveda and Pharma Research, 2015)
Uterine fibroid, a noncancerous growth of the uterus that often appear during childbearing age of female and it is one such gynecological disorder which is posing a major health problem. Regardless of benign neoplastic character, uterine fibroids are responsible for significant morbidity in a large segment of the female population. Ayurvedic texts have described Mamsaja granthi which perfectly correlates with benign neoplasm on modern lines. The present study was carried out to evaluate the role of Jalakumbhi Churna in the treatment of uterine fibroid. 30 female patients in reproductive age group who were suffering from uterine fibroid were registered for the present research work. 30 patients were divided equally into 2 groups, 15 patients were treated with Trail group drug i.e. by Jalakumbhi churna 6gm BD for 2 months and 15 patients were treated with Control group drug i.e. Nagakesar churna 6gm BD for 2 months. The diagnoses of uterine fibroids of patients were confirmed by clinical as well as investigation findings. After conducting clinical trial on 30 patients, observation and results were obtained. Statistical analysis shows that both trail and control drug were significantly effective to reduce the cardinal symptoms. As compared to Control drug the effect of Trail drug is better to reduce subjective and objective parameters. Results shows 20% patients were cured and 80% patients were improved after second follow up in trial group, while 26.66% patients were improved and 73.33% patients were not cured after second follow up in control group. Present study concludes that trail drug can definitely be used as adjuvant drug in the management of uterine fibroids.